Neutralization of BA.4–BA.5, BA.4.6, BA.2.75.2, BQ.1.1, and XBB.1 with Bivalent Vaccine - Zou, Jing; Kurhade, Chaitanya; Patel, Sohil; Kitchin, Nicholas; Tompkins, Kristin; Cutler, Mark; Cooper, David; Yang, Qi; Cai, Hui; Muik, Alexander; Zhang, Ying; Lee, Dung-Yang; et al. (The New England journal of medicine, 2023)
Participants who had received three doses of BNT162b2 vaccine received either a fourth dose or a bivalent vaccine containing BA.4–BA.5 mRNA; the latter group had higher neutralization against omicron variants.